Direct conversion of γ, γ-dicarbonyl-substituted aldehydes into γ-lactones with a sodium chlorite/DBDMH combination. Issue 11 (17th May 2017) - Guo, Yanjun; Xia, Aibao; Meng, Chenhong; Xu, Zhenyuan; Xu, Danqian
Abstract : An unprecedented and challenging simultaneous carboxylation/halogenation, and next lactonization of γ, γ-dicarbonyl-substituted aldehydes has been realized using a NaClO2 /DBDMH combination. Abstract : An unprecedented and challenging simultaneous carboxylation/halogenation, and next lactonization of γ, γ-dicarbonyl-substituted aldehydes has been realized using an eco-friendly, safe and inexpensive solid sodium chlorite (NaClO2 )/1, 3-dibromo-5, 5-dimethyl-hydantoin (DBDMH) combination. This new reaction is amenable to a multi-gram scale-up with high yield.